KOLABORASI PENDIDIK DENGAN ORANG TUA DALAM MENINGKATKAN PRESTASI PESERTA DIDIK - Rinaldi Datunsolang; Putriani L. Maliki (LP2M IAIN Sultan Amai Gorontalo, 2023)
This article aims to see how the collaboration of educators and parents improves student achievement. The method used in this research is a library research study where the data in this research is constructed from various literature, both online and in print. Then the data is classified and analyzed using a philosophical approach. The results of the study found that in the collaboration carried out by educators and parents there were several models that could be used as a solution to improve student achievement, namely visits to students' homes, inviting parents to school, holding correspondence between school and family, mutual support between educators and parents